The Learning of Rugby Passing Based on Different Small-Sided Games - Flávio Luiz Mazzeu; Flávio Henrique Bastos; Alexandre Moreira; Umberto Cesar Corrêa (Asociación Española de Ciencias del Deporte, 2021)
The small-sided, conditioned or reduced games refer to an instructional activity in which coach organizes the practice by reducing the complexity of the learning subject to the formal game. This study investigated the learning of rugby passing based on the practice of different small-sided games. Participants were 31 individuals of both sexes (23.0 ± 4.0 yr.) with no experience with rugby. The design involved three groups according to the practice/training format: 2 vs. 0, 1 + 1 vs. 1 and 2 vs. 1. The acquisition phase was carried out in three consecutive days with the performance of 60 trials of passing to the right side and 60 trials to the left side. The transfer phase was held on the last day by performing 20 trials. Performance measures involved passing direction, passing accuracy, running direction, passing zone and overall performance. Results showed that the 1 + 1 vs. 1 group was the only one that improved performance regarding the direction and accuracy of the pass in the acquisition phase and kept it in the transfer test. It was concluded that the small-sided game 1 + 1 vs. 1 made the learning of rugby passing possible.